Total Asset Turnover and Debt to Equity Ratio on Pharmaceutical Company Stock Prices: An Exploration of the Moderator Roles of Operating Efficiency - Nur Azizah; Syamsul Ridjal; Muhammad Irfai Sohilauw (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
High or low stock prices are a representation of the financial manager's performance in managing the company's internal factors. This research aims to investigate total asset turnover (TATO) and debt to equity ratio (DER) on stock prices with strong operational efficiency as moderation, as many as seven pharmaceutical sector issuers listed on the Indonesia Stock Exchange were used as the population by utilizing financial reports for 2015 - 2022. Total sampling technique was used to obtain 56 units of analytical data. Hypothesis testing was carried out using moderating regression analysis utilizing Eviews-13. The results of hypothesis testing show that total asset turnover (TATO) and debt to equity ratio (DER) have a positive and significant effect on stock prices. The role of moderation operational efficiency in testing total asset turnover is proven to be a moderating variable, whereas the debt to equity ratio test on stock prices does not work.